1997
DOI: 10.1016/s0167-5699(97)01002-5
|View full text |Cite
|
Sign up to set email alerts
|

A role for secretory phospholipase A2 and C-reactive protein in the removal of injured cells

Abstract: A role for secretory phospholipase A2 and C-reactive protein in the removal of injured cells Hack, C.E.; Wolbink, G.J.; Schalkwijk, C.G.; Speijer, H.; Hermens, W.Th.; van den Bosch, H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
2
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(97 citation statements)
references
References 43 publications
2
89
2
4
Order By: Relevance
“…It has recently been suggested that C-reactive protein binds to LPC in membranes of injured cells, thereby activating the complement cascade. 27 Thus, C-reactive protein, which is elevated in the blood in inflammatory conditions, is a potential candidate for an LPC-complexing protein, a possibility presently under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been suggested that C-reactive protein binds to LPC in membranes of injured cells, thereby activating the complement cascade. 27 Thus, C-reactive protein, which is elevated in the blood in inflammatory conditions, is a potential candidate for an LPC-complexing protein, a possibility presently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…27 Clearly, studies of the role of anti-LPC antibodies in chronic inflammation and atherosclerosis could shed light on this issue. Taken together, it is possible that LPC, produced during oxidation or enzymatically by PLA 2 , may activate B cells to antibody secretion and thus participate in and promote the chronic inflammatory reactions seen in atherosclerosis and several types of immunological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is an inflammatory marker that can promote the phagocytosis of injured cells and tissue remnants in combination with other proteins, thus increasing inflammation and tissue damage (20). It is hypothesized that periodontitis may alter the lipid profile and CRP levels in obese and normal weight individuals, but controlled clinical studies are still required to clarify these relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an elevated CRP signifies ongoing activation of inflammation that characterizes unstable coronary artery disease and may be one of the causal factors of instability. 4 Microalbuminuria even in healthy individuals is a risk factor for chest pain associated with cardiovascular events. The pathophysiologic mechanism underlying the association between albumin excretion and CVD is not fully understood.…”
Section: Introductionmentioning
confidence: 99%